INCIDENCE AND MANAGEMENT OF RUPTURE UTERUS IN OBSTRUCTED LABOUR - Khooharo, Yasmeen; Yousfani, Jabeen Zubair; Malik, Sara Haider; Amber, Aneela; Majeed, Numan; Malik, Nimra Haider; Pervez, Hira; Majeed, Isra; Majeed, Naeem (Journal of Ayub Medical College Abbottabad, 2013)
Background: Obstructed labour with ruptured uterus is a serious obstetrical complication with a high incidence of maternal and foetal morbidity and mortality. This study was conducted to find out the incidence of uterine rupture particularly in the patients of obstructed labour (OL), foeto-maternal outcome of such patients, and its management. Methods: This two year descriptive study was conducted in the Department of Obstetrics and Gynaecology Unit-I, at Muhammad Medical College Hospital from 1st January 2007 to 31st December 2008, on 40 diagnosed cases of OL. Patients were admitted through Casualty or were admitted in ward. Patients with previous caesarean section and myomectomy were excluded. Results: Ruptured uterus was found in 8 out of 40 patients of obstructed labour, they were relatively elder and grand-multiparous. Mean age of the patients was 36.5 years, while parity ranged between 5 and 12. Only one (12.5%) patient was primigravida with mean gestational age of 39.15 weeks. Seven (87.5%) patients had abdominal pain and tenderness, 5 (62.5%) vaginal bleeding, and 2 (25%) had shock. All cases were immediately managed with fluid replacement, blood transfusion and surgery. Six (75%) cases were diagnosed as ruptured uterus on clinical features while 2 (25%) with incomplete rupture were diagnosed on caesarean section for obstructed labour. Foetal mortality rate was high (7, 87.5%); 5 (62.5%) were fresh stillbirth and 2 (12.5%) died in nursery. Only 1 (12.5%) baby survived. There was 1 maternal death due to puerperal sepsis. Conclusion: The incidence of rupture uterus in obstructed labour was 20%. Immediate intervention is important factor for successful management of uterine rupture. Keywords: Obstructed labour, rupture uterus, hysterectomy, maternal mortality, foetal mortality